The Influence Of Compensation And Work Environment On Employee Performance With Job Satisfaction As An Intervening Variable - Roedyati, Joevi; Gettik Andri Purwanti (Smart International Management Journal, 2025)
This study aims to examine the extent of the influence of compensation and work environment on employee performance with job satisfaction as an intervening variable. Using primary data obtained through questionnaire collection with a sample of 56 employee respondents. The method used in this study is Structural Equation Modeling (SEM) analysis with Partial Least Square (PLS). The results of this study conclude that compensation has a positive and significant effect on job satisfaction (t-statistic 2.059 > t-table 1.96; p = 0.044). The work environment also has a significant effect on job satisfaction (t-statistic 3.096 > t-table 1.96; p = 0.003). However, compensation (t-statistic 1.054 < t-table 1.96; p = 0.297) and work environment (t-statistic 0.853 < t-table 1.96; p = 0.397) do not have a significant effect on employee performance. Job satisfaction significantly affects performance (t-statistic 4.617 > t- table 1.96; p = 0.000). The work environment significantly affects performance through job satisfaction (t-statistic 2.227 > t-table 1.96; p = 0.030). 1) That partially, there is a significant positive effect of compensation on job satisfaction and the work environment on job satisfaction. Whereas compensation towards employee performance and work environment towards employee performance are partially positively insignificant. This indicates that partially, there is a positive and significant relationship between job satisfaction and employee performance, job satisfaction does not mediate compensation on employee performance, and job satisfaction mediates the work environment on employee performance.